Fulfillment of Prisoners' Livelihood and Its Impact on Families from the Perspective of Maqashid Al-Syariah (Study at Ternate Class IIA Penitentiary) - Mustafa, Abdul Rahman; Djalal, Marini Abdul; Nainggolan, Basaria (Rechtsvinding, 2025)
The limitations on movement and access for husbands who are prisoners create a dilemma between the legal and sharia obligations to provide for their families and the reality of the limitations faced during detention. The purpose of this study is to analyze the mechanism for fulfilling prisoners' livelihoods for their families, examine the impact of the inability to fulfill livelihoods on the family, and analyze and critique the Maqhasid Al-Syar'iah aspects in fulfilling prisoners' livelihoods and their impact on the family. This research method is empirical legal research with a sociological approach to law and sharia. Data analysis techniques use qualitative analysis. The results of the study indicate that the fulfillment of prisoners' livelihoods is met through: the use of joint assets, the prisoner's income, the wife's employment, and through an assimilation program. The impact of the inability to fulfill prisoners' livelihoods on their families is: economic impact, psychological impact and divorce. From the perspective of maqashid al-shariah, the fulfillment of livelihood is related to maintaining the necessities of life, namely maintaining religion, life, mind, descendants and property. The application of the concept of Mubadalah or mutual assistance, where the wife is also responsible for earning a living by considering the condition of the husband who is a prisoner, is a solution that brings benefits to the prisoner's family.